Pubertal period influence on sports results among 13-14 year-old boys swimmers - Yuzhikova, O.; Kashirskaya, E.; Dorontsev, A.; Gladenkova, V.; Pavlova, S. (BIO Web of Conferences, 2020)
The aim of this research work was to reveal specific peculiarities of young swimmers training, taking into account their pubescence in terms of the long-term training concept. During the research it was defined that methodological support of spots training for a long-term period should contain not only prognostic model of prospective results achievement. It also should analyze individual peculiarities of pubertal period. During the research we used the official results of competitions protocols, the results of general and special physical readiness tests, resume of the leading swimming coaches. For statistical data handling we used quantitative variables, presented in a form ± of a standard error of the mean value (M ± m). The results were considered as statistically significant in terms of p < 0,05. Correlation analysis is realized using Pearson correlation coefficient. The held research helped to define typical characteristics of pubertal period in teen-agers swimmers, timely correct the training process. It was stated that athletes adaptation to the training and competitive loads in pubertal period was characterized by different degree of sports results increase and correlated with the intensity of hormonal changes. The boys with distinct features of pubertal period were the leaders at short distances, but showed coordinating abilities decrease. The athletes, whose somatic-gender changes didn`t have extreme indices or had prolonged duration, showed stable sports results increase mainly at long distances.